Characterizing the inpatient care of young adults experiencing early psychosis: A medical record review. Issue 2 (31st July 2017) - Puyat, Joseph H.; Kamieniecki, Renata; Vaughan, Brenda; Mihic, Tamara; Bonnie, Kofi; Danielson, Jeffrey; Williams, Sierra
Abstract : Aim: To characterize the inpatient care received by individuals experiencing early psychotic episodes in an inner city hospital. Method: Medical records of patients admitted between April 01, 2013, and March 31, 2015, to a psychiatric ward at an inner city hospital were retrospectively examined. Included in the study are patients who were 25 years of age or younger and were hospitalized for psychotic symptoms. Demographics and health service use were summarized using descriptive statistics. Results: A total of 73 inpatients (mean age = 22; males =78%; Caucasian = 41%) met the study inclusion criteria with a combined total of 102 care episodes and an average length of stay of 32.6 days. Monitoring of vital signs (VS) and mental status examinations (MSE) were performed in most care episodes although these were not performed regularly (daily VS checks—31%; MSE every nursing shift—18.6%). In 49% of the care episodes, patients were discharged on long‐acting injectable antipsychotics. Even when indicated, not all care episodes had follow‐up appointments (82.8%) in the community. The use of seclusion was higher in the wards (32%) than in the emergency department (21%), whereas the use of restraints was higher in the emergency department (16%) than in the wards (<1%). Conclusions: There is wide variation in the rate at which various clinical care processes are performed and in the provision of inpatient care to younger adults experiencing episodes of early psychosis. Consistent standards of care are needed to reduce variations and improve treatment outcomes and experiences.